Pemodelan Hubungan Tinggi dan Diameter Eucalyptus pellita Umur 30 Bulan - Tatik Suhartati; Sugeng Wahyudiono; Michael; Purwadi (Jurnal Wana Tropika, 2023)
Inventory on Plantation Monitoring Assessment (PMA) Eucalyptus pellita at the aged of 30 months, measuring total height (h) and diameter at breast height (dbh). Height measurements were done using the Vertex. Measuring the total height of a tree whose crown has started to close (overlap)Â  requires more time to find the highest point of the tree, it is necessary to overcome it with a tool that is a height estimator model through the relationship between height and diameter at breast height (h-dbh). The study was conducted using two compartments of Eucalyptus pellita stands at the aged of 30 months. Sampling conducted by Systematic Sampling with Random Start. The data measured were total height (h) and diameter at breast height (dbh). Simple linear regression modeling h-dbh compiled for each compartment then carried out a goodness of fit test and validation using the Bias, SA and SR values, after that the regression line similarity was tested. The results showed that the two compartments have regression equations with the same slope and intercept, so that the two compartments can be threated as one dataset and the total height in the two compartments studied can be estimated using the equation h = 6,968 + 0,844 dbh.